Economic Impact Assessment of Mega-Events in the United Kingdom and Brazil. (September 2019) - Wan, Shui Ki; Song, Haiyan
Hosting mega-events is often perceived as a way to stimulate economic growth through tourism. However, the cost of infrastructure investments and promotion may outweigh the benefits generated by the mega-events. Measuring the impact of such events on a hosting country's economy is not easy, especially as mega-events generally involve many sectors of a destination's economy. In this study, we adopt a panel data approach to evaluate the impact of the London Olympic Games, Brazil World Cup, and Rio Olympic Games on the economic growth of the respective destinations. Using cross-sectional correlations between countries, we construct scenarios in which the hosting countries did not hold the mega-events and then estimate the time-varying impact of the events on the economy. The developed and developing countries exhibit different results.